Clinical application of mixed reality holographic imaging technology in scaling and root planing of severe periodontitis: a proof of concept - Xue, Fei; Zhang, Rui; Dai, Jun; Zhang, Yong; Luan, Qing-Xian (Journal of dentistry, 2024)
To demonstrate the potential application of mixed reality (MR) holographic imaging technology in subgingival scaling and root planing (SRP) for patient with advanced periodontitis. This case series comprised the analysis of 1566 sites from 261 teeth of 10 patients with advanced periodontitis. Digital CBCT scans and intraoral scans of the patients were digitally acquired preoperatively and aligned to create a three-dimensional periodontal visualization model. Through rendering, interactive holographic images were displayed using MR. The surgeon first used MR images to communicate with the patients, and then facilitated SRP under their guidance. Probing pocket depth (PPD), clinical attachment loss (CAL), Plaque index (PI), and bleeding on probing (BOP) parameters were recorded at baseline and at 8-week postoperatively. Patient-reported outcome indicator questionnaires on self-efficacy were also collected. PPD, CAL, PI, and BOP significantly decreased at 8-week following MR hologram-assisted SRP (p<0.001). For sites with PPD≥4 mm, PPD and CAL declined by 2.33±1.23 mm and 0.69±1.07 mm, respectively. PI significantly decreased from 1.94±0.61 to 0.82±0.58 (p < 0.001) and BOP sites decreased significantly from 84.11% to 40.25%. After receiving MR holograms for condition communication, most patients had a better perception of the effectiveness of SRP treatment and the benefits it brings. 80% of the subjects expressed their willingness to undergo MR-assisted periodontal treatment in the future. These results provide preliminary support for MR hologram-assisted digital SRP. With this technology, images of the gingiva and alveolar bone can be displayed in real time, accurately and three-dimensionally. This improves SRP effectiveness, diminishes complications, and enhances patients' confidence in the treatment. MR holographic imaging-based digital SRP is a clinically feasible and promising adjunctive periodontal treatment option. It may contribute to improved non-surgical treatment efficacy in patients with severe periodontitis.